Analysis of Quality Control of Instant Mie Products Using C-Chart Methods (PT XYZ) - Endah Wahyuni, Ayu; Noor Fadillaah, Anna; Rahmana, Arief (International Journal of Psychosocial Rehabilitation, 2020)
This study looked at instant noodle products with bag-noodle and cup-noodle types at PT XYZ. Both products address a fairly high defect rate based on company standardization, including the shape and structure of the product. This resulted in not achieving production targets. Therefore, supervision of the production process is very necessary to minimize the number of defective products. The C-Chart method is a solution to determine the level of product damage in the production process. Thus, the purpose of this study is to provide information about product quality based on the level of damage so that the production process can run effectively and efficiently.